Copper/Di-tert-butyl Peroxide-Catalyzed Regioselective Hydroxyphosphorylation of 1,3-Enynes - Zhu, Shaoqun; Wang, Jiawei; Zhou, Bing; Hou, Hong (Synthesis, 2021)
The copper/di-tert-butyl peroxide-catalyzed regioselective hydroxyphosphorylation of 1,3-enynes is described. The advantages of the reported radical reactions are excellent functional group tolerance, the use of a catalytic amount of copper and di-tert-butyl peroxide (tBuOOtBu) as a radical initiator, and mild reaction conditions. The desired products are obtained in moderate to excellent yields after purification.
Keywords: copper catalysis; regioselectivity; radicals; hydroxyphosphorylation; 1,3-enynes